USING “DRAW THE TEACHER” GAME IN TEACHING VOCABULARY FOR ELEMENTARY SCHOOL STUDENTS - Resti Juni Astuti; Yuli Tiarina (Journal of English Language Teaching, 2013)
This article was written to describe the procedure of using Draw the Teacher game in teaching vocabulary for elementary school students. The use of translation method and memorize technique done by the teacher in teaching vocabulary is not effective. As the result, the students tend to easily get bored and do not give attention during teaching learning process. By using this game, it is hoped that the students will enjoy in learning English especially in learning vocabulary. During the game, the students are asked to do the instructions given by the teacher to draw the teacher’s body parts. Here, they will learn vocabulary related to the name of body’s parts. In addition, drawing is the main activity in this game. This activity not only can make students fun in the classroom, but also can enhance students’ cognitive development and memory retention. Abstrak Artikel ini ditulis untuk mendeskripsikan prosedur penggunaan permainan Draw the Teacher dalam mengajarkan kosakata pada siswa sekolah dasar. Penggunaan metoda terjemahan dan hafalan dalam mengajarkan kosakata selama ini dianggap kurang efektif. Akibatnya, siswa sekolah dasar cenderung untuk merasa bosan dan tidak memberikan perhatian penuh selama proses belajar mengajar. Dengan permainan ini diharapkan siswa dapat menyukai pelajaran bahasa Inggris terutama dalam pembelajaran kosakata. Selama permainan, siswa diminta untuk melakukan instruksi yang diberikan guru berupa menggambar bagian tubuh dari guru. Siswa akan belajar mengenai kosa kata yang berhubungan dengan nama bagian-bagian tubuh. Selain itu, menggambar merupakan kegiatan inti dari permainan ini. Selain menyenangkan, menggambar dapat meningkatkan perkembangan kognitif dan kemampuan memori siswa.